Urban air pollution : (Springer, 1996)
The air pollution problem is widespread throughout the world and the elimination of the risks to human health is of paramount importance. Urban areas are one of the major sources of air pollution having characteristic patterns of pollutant emissions, with adverse consequences to the health of their inhabitants.